2014
DOI: 10.1111/tmi.12324
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic determinants and inequities in coverage and timeliness of early childhood immunisation in rural Ghana

Abstract: Abstractobjectives To assess the extent of socio-economic inequity in coverage and timeliness of key childhood immunisations in Ghana.methods Secondary analysis of vaccination card data collected from babies born between January 2008 and January 2010 who were registered in the surveillance system supporting the ObaapaVita and Newhints Trials was carried out. 20 251 babies had 6 weeks' follow-up, 16 652 had 26 weeks' follow-up, and 5568 had 1 year's follow-up. We performed a descriptive analysis of coverage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
76
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 25 publications
10
76
1
5
Order By: Relevance
“…(27,33) Many studies have shown marked differences in age-appropriate and 'upto-date coverage' by socioeconomic status. (34,35) In this relatively homogenous study setting, we also find significant location-specific and year-to-year variation in timeliness.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…(27,33) Many studies have shown marked differences in age-appropriate and 'upto-date coverage' by socioeconomic status. (34,35) In this relatively homogenous study setting, we also find significant location-specific and year-to-year variation in timeliness.…”
Section: Discussionmentioning
confidence: 59%
“…Socio-economic factors also contribute to inequities in coverage and time to vaccination. (34,35) though these are hard to characterise reliably in a relatively homogenous rural population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in SSA analyzing parental characteristics associated with the vaccination status of their respective children have largely focused on other socio-demographic factors. Variables such as parental education [4,[17][18][19][20][21][22][23], mothers' age [18,19], household income or wealth [4,11,17,19,22,24], family size or mothers' parity [4,[17][18][19], religion of caregivers [25,26], and location of labor and delivery [23] are well documented as correlates with the vaccination status of a child. We are only aware of four published studies conducted in SSA in the past 15 years that assessed KATCI [18,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting AORs for this less frequent outcome thus approximated more closely to risk or rate ratios. Model building was informed by a hierarchical framework5 of the determinants of vaccination identified a priori 3 4 13 14. We initially fit a model comprising distal determinants (religion, ethnicity, socioeconomic status (SES), maternal occupation, maternal education, vaccine due in wet season, infant sex); then added intermediate determinants (maternal age/family size, maternal illness in the year before delivery, distance to the nearest health facility, place of delivery, multiple birth), followed by birth weight and, finally, infant illness, a possible mediator of the association between birth weight and vaccination.…”
Section: Methodsmentioning
confidence: 99%
“…Substantive socio-demographic inequities in vaccination remain 2. Many infants are vaccinated late 3 4. The latest global vaccination policy highlights the need to identify and target those underserved by vaccination in order to increase equity and uptake 2…”
Section: Introductionmentioning
confidence: 99%